2020
DOI: 10.1007/s40204-020-00136-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of tannic acid-enriched materials modified by poly(ethylene glycol) for potential applications as wound dressing

Abstract: The interests in the biomedical impact of tannic acid (TA) targeting production of various types of biomaterials, such as digital microfluids, chemical sensors, wound dressings, or bioimplants constantly increase. Despite the significant disadvantage of materials obtained from natural-based compounds and their low stability and fragility, therefore, there is an imperative need to improve materials properties by addition of stabilizing formulas. In this study, we performed assessments of thin films over TA prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…It should, however, be noted that an increased number of hydroxyl groups in the resulting biomaterials determines elevated water binding. It is highly desirable that the moisture environment is constantly maintained, avoiding skin dehydration and scar formation during wound healing, as previously shown [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be noted that an increased number of hydroxyl groups in the resulting biomaterials determines elevated water binding. It is highly desirable that the moisture environment is constantly maintained, avoiding skin dehydration and scar formation during wound healing, as previously shown [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tannic acid (TA) is a natural polyphenolic compound extracted from plants, composed of a central glucose connected to five digalloyl ester groups. Various studies have found that TA exhibits antibacterial, antioxidant, anti-inflammatory, and hemostatic properties, which are beneficial for accelerating wound healing [ 7 , 8 , 9 ]. Additionally, because of its good aqueous solubility, the bioavailability of TA is higher than other natural antimicrobials, such as curcumin, peppermint, cinnamon, and thymol [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the crosslinking degree, iron was also added to the formulation. Indeed, the additional crosslinking by metal complexation with iron (III) was found to improve the physical properties of chitosan films while increasing the metabolic activity of cells cultured on the material surface [ 15 ]. Moreover, tannic acid–iron (II) complex was also reported as a coating of artemisinin-zeolite nanoparticles, displaying low toxicity towards normal L929 human cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%